Effectiveness and safety of Blefarovit cosmetic product usage in patients with chronic blepharoconjunctivitis and «dry eye» syndrome, combined with an active demodicosis component - D.Yu. Maychuk; А.О. Loshkareva (Офтальмохирургия)
Purpose. Comparative analysis of the efficacy and safety of Blefarovit product in the complex therapy of chronical blepharoconjunctivitis and «dry eye» syndrome with a pronounced demodicosis component in patients, previously received standard treatment with or without short-term positive effect. Material and methods. The present study included 60 patients (120 eyes) with chronical blepharoconjunctivitis, «dry eye» syndrome and demodicosis component. The patients, involved in the study had pronounced thickening of the eyelid margin, scabs and «clutches» in the eyelashes, meibomeitis, hyperemia, follicular reaction of the tarsal and bulbar conjunctiva. This study was devoted to finding a new approach for the demodecosis component therapy, using staged eyelid hygiene technology with the multicomponent product Blefarovit. The purpose of this study was to estimate efficacy and safety in isolated Blefarovit usage (1st stage of therapy) and Blefarovit in the combination with anti-inflammatory and artificial tears therapy (2nd stage of therapy). Results. The results of the study were increasing of the TBUT test and decreasing the of Demodex Folliculorum number. Conclusion. The usage of Blefarovit product made possible to show significant decreasing in the severity of the demodectic component without increasing the toxico-allergic background.